Diazinon degradation by bacterial endophytes in rice plant (Oryzia sativa L.): A possible reason for reducing the efficiency of diazinon in the control of the rice stem–borer. (May 2020) - Nasrollahi, Mina; Pourbabaei, Ahmad Ali; Etesami, Hassan; Talebi, Khalil
Abstract: It is well known that microorganisms can reduce the effectiveness of organophosphate pesticides after their application. But, little information is available concerning the effect of rice endophytic bacteria on the degradation of diazinon, an organophosphate pesticide used in control of the rice stem–borer, absorbed by the rice plant. Thus, aim of this study was to characterize the endophytic bacterial isolates, isolated from diazinon–treated and non–treated rice plants in paddy fields, in terms of diazinon degradation and to investigate whether potent isolates that degrade diazinon in vitro might have the same effect in the rice plant. The results showed that all endophytic isolates, isolated from both groups of rice plants (diazinon–treated and non–treated rice plants), could grow in mineral salt medium (MSM) supplemented with diazinon (20 mg L −1 ) as a sole carbon source, and 3.79–58.52% of the initial dose of the insecticide was degraded by the isolates within 14 d of incubation. Phylogenetic analysis based on 16 S rRNA sequencing indicated that the potent isolates (DB26–R and B6–L) clearly belonged to the Bacillus genus. The diazinon concentrations in rice plants co–inoculated with B. altitudinis DB26–R and B. subtilis subsp. Inaquosorum B6–L and single–inoculated with these strains were reduced significantly compared with endophyte–free rice plants. These results provide unequivocal evidence that the rice endophytic bacteria, in addition to in vitro degradation of diazinon, are also involved in the rapid inactivation of diazinon in rice plants treated with diazinon ( in vivo degradation of diazinon). Graphical abstract: Image 10247 Highlights: Endophytic bacteria from diazinon treated and non treated rice degraded diazinon. Diazinon degrading endophytic bacteria could degrade diazinon in rice plants. The highest decrease in diazinon concentration was observed in co-inoculated rice.